Achieving High Fill Factor via Increasing Interfacial Disorder to Inhibit Bimolecular Recombination for Efficient Organic Solar Cells - He, Dan; Xie, Linwei; Bai, Yahui; Zhang, Huotian; Liu, Liping; Kong, Jingyao; Chai, Yongqiang; Li, Xiaojun; Wang, Mengni; Zhang, Yajie; Zhang, Jianqi; Li, Yongfang; et al. (Angewandte Chemie International Edition, 2025)
The inferior fill factor (FF) is one of main reasons impeding further improvement of power conversion efficiencies (PCEs) in organic solar cells (OSCs). But no theoretical framework for high FFs has been established yet. Herein, an efficient strategy is developed to enhance FFs via introducing a small molecule, CNDT, into active layer to increase electron donor/acceptor interface disorder, raise energy barrier for charge back transfer, and thus reduce bimolecular recombination rate constant (krec). CNDTs tend to distribute over donor/acceptor interfaces and disturb molecular stacking of Y6 to deliver more disordered donor/acceptor interfaces but higher crystal quality in the D18:Y6+ blend film, compared to D18:Y6. Altogether, in the D18:Y6+ blend film, a higher energy of charge transfer state magnifies energy barrier for charge recombination to decrease charge recombination rate/ratio and reduce krec, inhibiting bimolecular recombination in devices. Therefore, FFs of OSCs are improved from 75.78% (D18:Y6) to 81.13% (D18:Y6+), yielding a higher PCE of 19.45%. Moreover, D18:L8-BO+ based OSCs feature FFs over 83%, a record for OSCs so far. PCE increases subsequently to 19.80%. It demonstrates that increasing interface disorder without sacrificing crystal quality enhances energy barrier of charge recombination and inhibits bimolecular recombination to efficiently improve FFs for higher PCEs.
CRIS-Team Scopus Importer:2025-05-23
Keywords: Charge carrier recombination; Donor/acceptor interfaces; Fill factors; Organic solar cells